Detecting Unauthorized Access of Personal Device - kumar, S. Jerald Nirmal; Srinivasan, Aravindan; V. Sasirekha, V. Sasirekha; Ramasamy Reddy, Viswanathan; T. Vengatesh, T. Vengatesh (Journal of Neonatal Surgery, 2025)
Unauthorized access to personal devices poses a severe concern to people's security and privacy in the digital age. The primary objective of this endeavour is to develop a dependable system for detecting and preventing such unauthorized access. The proposed system employs an interdisciplinary approach that integrates behaviour analysis, anomaly detection, and advanced authentication mechanisms. The system has robust authentication techniques, such as biometric identification and two-factor authentication, to ensure that only authorized users are allowed access. From then, users' interactions with the device are monitored through continuous behaviour analysis, which creates a baseline of normal behaviour. In the case that this baseline is deviated from, a warning signalling potential unauthorized access is issued. Algorithms for anomaly detection also identify peculiar behaviours or patterns, which enhances the system's ability to identify security breaches and respond quickly. Furthermore, the system incorporates machine learning models that adapt over time to new threats and emerging patterns. Updates and patches are frequently published to stay up to date with emerging attack methods. The proposed solution aims to safeguard confidential information and preserve user privacy in an increasingly interconnected environment by implementing this comprehensive approach and providing a proactive barrier against unauthorized access to personal devices.